The story of Japan's Ohmi merchants : - Suenaga, Kunitoshi (Japan Publishing Industry Foundation for Culture (JPIC), 2019)
Ohmi merchants can be considered the very source of Japanese-style management. The key concepts that they developed underpinned the success of Japanese corporations for generations. These include core concepts such as sanpo-yoshi or “three-way satisfaction” and corporate social responsibility (CSR), considering a third-person perspective, being a member of society, a healthy tension with society, customer satisfaction, contribution to society, the social consciousness of “good for the world”, appropriate profits, avoid waste and give your all, the spirit of the peddler, faith and devotion, talent and innovation, leveraging information and investing in startup ventures.